Merevitalisasi Kembali Remaja Masjid untuk Meningkatkan Sholat Berjamaah di Masjid pada Tiga Dukuh di Desa Bungkuk Kecamatan Parang Magetan - Andhita Risko Faristiana; Bagas Muhyidin Abid; Ranna Anggit Melati (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
This research is research by IAIN Ponorogo students conducted by the KPM 19 group in Bungkuk village, Parang, Magetan. This KPM aims to be media for learning, practice, and society. Understanding of students in managing human resources to improve the quality and critical thinking patterns of each individual so that they become good individuals. The method used is the asset-based community development (ABCD) method. The ABCD approach involves five steps, including the processes of discovery, dreaming, planning, determining, and implementing. For this reason, it aims to provide character and activities that are beneficial to the community. Based on the potential according to initial observations, inviting Bungkuk Village youths to participate in enlivening the mosque in their respective hamlets because of the potential, to increase the sympathy of Bungkuk Tiga Village youth towards the mosque in their respective hamlets, it's not just congregational prayers, but work programs that have been prepared by the BKM Mosque Welfare Board, in order to increase youth togetherness to revive youth youth organizations that have been passive.